A new, giant ricinuleid (Arachnida, Ricinulei), from the Pennsylvanian of Illinois, and the identification of a new, ontogenetically stable, diagnostic character. (May 2021) - Whalen, Niall; Selden, Paul
Abstract: A new fossil ricinuleid, Curculioides bohemondi n. sp., from the Pennsylvanian Energy Shale of Illinois is described from a single specimen. It is the largest ricinuleid species yet described, living or extinct. The Energy Shale represents a new geographic locale for fossil ricinuleids, a sparsely distributed group. The species is distinguished from other members within the genus by the possession of very large (0.09 mm) carapace tubercles at a very low (30 mm -2 ) density. Statistical analyses are performed on extant and fossil ricinuleids to determine how their tubercles change throughout ontogeny, culminating in the recovery of a new ontogenetically stable diagnostic character: the tubercle coefficient (a measure of the size of the tubercles relative to body size). UUID: http://zoobank.org/aa9f2de5-c49d-4f70-bba5-db12fdee406f .